1997
DOI: 10.1016/s0014-5793(97)00802-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential action of AGCF2 upon cell type‐dependent expression of human angiotensinogen gene

Abstract: To investigate the regulatory mechanisms of human angiotensinogen (ANG) gene expression in the brain, we analyzed the 1.3-kb promoter by transfection studies and gel shift assays. The region from -106 to +44 was sufficient for promoter activity in glioblastoma cells, and multiple nuclear factors including AGCF2 (human ANG core promoter binding factor 2) bound within this 150-bp region. The mutations within AGCF2-binding elements decreased the transcriptional activity in glioblastoma cells but rather increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We have identified various regulatory elements and factors that regulate human ANG gene transcription (12)(13)(14)(15)(16)(17)(18)(19). Our previous studies have shown that cis-acting elements located at nucleotides Ϫ1222 to ϩ44 are sufficient for human ANG gene expression in transiently transfected human hepatoma HepG2 cells and in the livers of transgenic mice (20,21) and that HNF-4 plays an important role in hepatic ANG expression (18).…”
mentioning
confidence: 99%
“…We have identified various regulatory elements and factors that regulate human ANG gene transcription (12)(13)(14)(15)(16)(17)(18)(19). Our previous studies have shown that cis-acting elements located at nucleotides Ϫ1222 to ϩ44 are sufficient for human ANG gene expression in transiently transfected human hepatoma HepG2 cells and in the livers of transgenic mice (20,21) and that HNF-4 plays an important role in hepatic ANG expression (18).…”
mentioning
confidence: 99%
“…AGCE1 was also shown to be required for the activity of an upstream AGT enhancer, ATF-like element (ALE) [44]. In addition to AGCE1, Yanai et al also describes two AGCE2 sites, located upstream and downstream of the transcription initiation site that show a possible cell-type-dependent function [45]. The hepatocyte nuclear factor 4 (HNF4) was also shown to potentiate human AGT (hAGT) promoter activity in HepG2 cells [46].…”
Section: Regulation Of Angiotensinogen Gene Expressionmentioning
confidence: 99%